Pelatihan Komputer Akuntansi Aplikasi Zahir Bagi Guru Smk Se Sumatera Barat - Riani Sukma Wijaya; Nini Nini; Khadijah Ath Thaira; Rahmaita Rahmaita; Eka Mariyanti (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
This training is carried out in order to fulfill the tri dharma of higher education at Dharma Andalas University. The activities carried out are in the form of computer accounting training for Zahir applications for SMK teachers throughout Sumatra. cash and cash receipts and cash disbursements. The participants who took part in this training were SMK teachers throughout Sumatra who were given this training by approximately 22 teachers. The training is carried out in a tutorial and ends by giving a case. After the case is completed, an evaluation will be carried out regarding the use of the software for the teacher. After this training was held, 90% of teachers were able to understand the zahir application and the remaining 10% there were still teachers who did not understand the use of the zahir application.